A method to realize high-precision and large laser thermal bending angle. (February 2021) - Guo, Yankuo; Shi, Yongjun; Wang, Xiaogang; Sun, Rui; Li, Xianfa
Abstract: Laser thermal bending under preload is a new direction of laser thermal bending research, which has many advantages such as increasing the bending angle and controlling the bending direction. Under the background of high efficiency and preciseness pursued by state and enterprises, a new method to realize high- precision and large bending angle is proposed on the basis of preload. In this method, the equation is simplified reasonably, then the precision of this equation is corrected by experiment, and finally the high-precision equation is obtained. Through this high-precision equation, any combination of parameters (preload, scanning position, plate length, plate width) can achieve any high-precision bending angle. The bending angles obtained by this method are compared with the experimental values, and the results show that the errors are less than 0.56 %. The bending angles obtained by this method are compared with the paper, the errors are less than 1.6 %. Therefore, the bending angle obtained by this method has high precision.